Dreams of joy : a novel - See, Lisa (Random House, 2011)
A continuation of "Shanghai Girls" finds a devastated Joy fleeing to China to search for her real father while her mother, Pearl, desperately pursues her, a dual quest marked by their encounters with the nation's intolerant Communist culture.